PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI DISTRIK NAVIGASI PALEMBANG - Sajad, Indriani; Supriyatno, Supriyatno (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2022)
This study aimed to determine the influence of education and training to increaseemployee performance in the Distrik Navigasi Palembang. The subjects were employeeDistrik Navigasi Palembang. Data were processed using Multiple Linear RegressionAnalysis. The results of the research showed that education and training variables haveinfluence on employee performance for 67.9% while the remaining 32% is explained byother factor. The conclusion was the education and training can affect employeeperformance improvement. Distrik Navigasi are advised to continue to develop educationand training for their employee so that the goals can be achieved.